A secure two-party PIR for privacy applications. (5th September 2022) - Bhat, Radhakrishna; Reddy, N.V. Subba
The major drawback of existing information retrieval schemes in preserving user privacy is that they either exhibit computationally bounded privacy with intractability assumptions or perfect privacy with high bandwidth utilisation. Today, the essential requirement is to have a bandwidth efficient perfect privacy preserving information retrieval scheme in order to provide effective and guaranteed service to the information retrieving user. Therefore, in this paper, we have constructed a new single database perfect privacy preserving private block retrieval scheme called as 'pepperPBR' using quadratic residuosity as the underlying primitive where private block retrieval (PBR) is a natural extension to private information retrieval (PIR). In this paper, user generates O (6 k ) bit query and server generates O (2 ku + o ( n )) bit response where n is the database size, o ( n ) is the non-trivial server communication cost, u is the number of database blocks, k is the security parameter.